2020
DOI: 10.3389/fnut.2020.570047
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Supported on Magnesium DiHydroxide (Resv@MDH) Represents an Oral Formulation of Resveratrol With Better Gastric Absorption and Bioavailability Respect to Pure Resveratrol

Abstract: Resveratrol attracts great interest because of the plethora of in vitro effects at the micromolar concentration range. Unfortunately, these effects are difficult to establish in vivo, due to the low concentration of resveratrol reached. This discrepancy is due to the molecules low solubility in water that favors the propensity for an intestinal absorption rather than in the gastric compartment. To address these challenges, we developed a Solid Dispersion of Resveratrol Supported by Magnesium Di Hydroxide formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…A human study showed that oral administration of RSV in one dose (180 mg/kg) can have a maximum concentration of about 2 μM. 37 However, administration of a RSV−magnesium dihydroxide formulation can have a maximum concentration of about 6 μM. 37 These concentrations may not be enough to achieve the 50% of inhibition on human 3β-HSD1.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A human study showed that oral administration of RSV in one dose (180 mg/kg) can have a maximum concentration of about 2 μM. 37 However, administration of a RSV−magnesium dihydroxide formulation can have a maximum concentration of about 6 μM. 37 These concentrations may not be enough to achieve the 50% of inhibition on human 3β-HSD1.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The bioavailability of RSV is relatively low, meaning that only a small proportion of the compound is absorbed into the bloodstream after ingestion. A human study showed that oral administration of RSV in one dose (180 mg/kg) can have a maximum concentration of about 2 μM . However, administration of a RSV–magnesium dihydroxide formulation can have a maximum concentration of about 6 μM .…”
Section: Discussionmentioning
confidence: 99%
“…The effective concentration of it in serum is only trace levels [ 33 ]. Therefore, a lot of teams are committed to developing new dosage forms, such as melt extrusion method for the high melting point of insoluble resveratrol slow-release solid dispersions, resveratrol with two magnesium hydroxide as the carrier (Resv @ MDH), resveratrol phospholipid complex self-microemulsion drug delivery system, etc., which significantly improve the solubility and bioavailability of resveratrol [ [34] , [35] , [36] ]. Additionally, Li et al [ 37 ] confirmed that dipalmitoylphosphatidylcholine-coated lipid nanoparticles (DPPC-LNs) as inhalable carriers could accumulate resveratrol in pulmonary vessels, which inhibited 5-hydroxytryptamine (5-HT)-induced proliferation of PASMCs, and 25–200 μM Res-DPPC-LNs had no effect on their viability.…”
Section: Traditional Chinese Medicine Monomers Inhibiting the Prolife...mentioning
confidence: 99%
“…The bioavailability of resveratrol is not reported in these studies but could be a potential reason attributable to the conflicting results. In general, oral resveratrol has low bioavailability but high absorption, due to a rapid hepatic first-pass metabolism [ 173 ]. Of note, the bioavailability of resveratrol can be greatly enhanced over 10 times by piperine, which is a type of bioactive alkaloid [ 174 ].…”
Section: What Is Known About Their Effect On Cardiac Aging and Cvd?mentioning
confidence: 99%